Bioprospecção em espécies de Inga (Fabaceae Mimosoideae) - Lima, Nerilson Marques [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The study of natural products as a source of new anticancer agents is very important, because even due to the large amount of existing drugs for the treatment of cancer, has not yet reached an optimal compound that has greater selectivity, fewer side effects, higher potency therapeutic and index of least resistance.One of thefamilies with recognized therapeutic potential is the Fabaceae family, whose chemosystematics show an abundance of flavonoid with broad spectrum of biological activities, including antitumor. Thus, the aim of this study was to isolate and characterize phenolic compounds from fractions obtained of the genus Inga (I. laurina, I. edulis and I. marginata) selected by bioassay cytotoxic and identify metabolites in mixture by HPLC-PDA, HPLC-MS, LC-SPE-TT and NMR Spectroscopy. The chemical composition of these species indicated a wide variety of aromatic acids, flavonoids, tannins and triterpenes. This work describe the characterization of the compounds: lupeol, fatty ester of -amyrin, the olean-18-ene ester and friedelin, vanillic acid, 3,4,5-trimethoxy benzoic acid, gallic acid, gallate methyl, p-coumaric acid, benzoic acid, p-hydroxybenzoic, protocateuico acid, tannic acid, caffeic acid, p-methoxycinnamic acid, p-hydroxybenzoic acid derivative methylated of 4-hydroxybenzoic acid, ferulic acid, myricetin, myricetin-3-Orhamnoside, myricetin-3-O- (2 -O-galoil) - -rhamnopyranoside, apigenin, quercetrin, proanthocyanidin A-2 and procyanidin B, 2-rhamnopyranosyl-3,5-dihydroxyphenyl gallate, 2-rhamnopyranosyl-4,6-dihydroxyphenyl gallateand 4-vinyl-phenol. Through the analysis by HPLC-PDA detected the presence of one anthocyanin from aqueous fraction in five other anthocyanins in the methanolic fraction from seeds of I. edulis. Through the bioassay-guided fractionation was possible to obtain a fraction with high antitumor potential (ED50 = 4.0 mg/mL) that was characterized such a mixture...

O estudo de produtos naturais como fonte de novos agentes anticâncer torna-se de grande importância, pois mesmo devido à grande quantidade de drogas já existente para o tratamento de neoplasias, ainda não se chegou a um composto ideal que tenha maior seletividade, menos efeitos colaterais, maior potência terapêutica e menor índice de resistência. Das famílias vegetais com reconhecido potencial terapêutico destaca-se a família Fabaceae, cuja quimiossistemática atesta para uma riqueza de compostos flavonoídicos com amplo espectro de atividade biológica, inclusive antitumoral. Desta forma, o objetivo principal deste estudo foi isolar e caracterizar substâncias fenólicas a partir de frações oriundas de espécies do gênero Inga (I. laurina, I. edulis e I. marginata) selecionadas através do bioensaio com linhagens de celulas antitumorais e identificar metabólitos em mistura através de CLAE-DAD, HPLC-MS, LC-SPE-TT e Espectroscopia de RMN. A composição química destas espécies indicou uma grande variedade de ácidos aromáticos, flavonóides, taninos e triterpenos. Este trabalho permitiu a caracterização das substâncias: lupeol, éster graxo da -amirina, éster do olean-18-eno, fridelina, ácido vanílico, ácido 3,4,5-trimetoxi-benzóico, ácido gálico, galato de metila, ácido pcumárico, ácido benzóico, p-hidroxi-benzóico, ácido protocateuico, ácido tânico, ácido cafeico, ácido p-metoxicinâmico, ácido p-hidroxibenzóico, derivado metilado do ácido 4-hidroxibenzóico, ácido ferúlico, miricetina,miricetina-3-O-ramnosídeo, miricetina-3-O-(2-Ogaloil)- -ramnopiranosídeo, apigenina, quercetrina, proantocianidina A-2, procianidina B, galato de 2-ramnopiranosil-4,6-diidroxifenila, galato de 2-ramnopiranosil-3,5-diidroxifenila e do glicosídeo do 4-vinil-fenol. Através das analises por CLAE-DAD detectamos a presença de uma antocianina altamente polar na fração aquosa...
Keywords: Ácido fenólico; Produtos naturais; Flavonoides; Cromatografia líquida de alta eficiência; Cancer; Flavonoids